From hydronyms to conservation: developing a sustainable model for river preservation with indigenous community engagement - Imelda Yance; Achril Zalmansyah; Asep Supriadi; Rita Novita; Evi Maha Kastri; Jahdiah; Rissari Yayuk; Syamsurizal; Zainal Abidin; Yenni Febtaria Wijayatiningsih (Cogent Arts & Humanities, 2024)
Hydronym, which pertains to the study of the names of rivers and riversheds, has a crucial role in maintaining the harmony of aquatic ecosystems and in preserving the biodiversity of rivers, swamps, lakes, forests, and even the sea. The present study aims to investigate the significance of hydronyms in Bengkalis Regency, Indonesia concerning river biodiversity conservation. Utilizing descriptive qualitative methodology, the study mainly involves gathering information on the names of rivers, including their language, meaning, and history. The study’s findings reveal that the hydronyms in Bengkalis Regency, Indonesia comprise geographical, social, cultural, and belief-related details that refer to the situation of the local people at the time of the river’s inception. Further investigation also discloses that the hydronyms represent the richness of the river’s biodiversity, which includes 24 native flora species and 4 native fauna species. The effectiveness of river biodiversity conservation involves maintaining native flora and fauna in their natural habitat by involving indigenous people, whose lives rely on the existence of these rivers. This study aims to fill the gap by utilizing the rich results of hydronym studies for purposes such as biodiversity conservation.